2013
DOI: 10.3390/w5041487
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Coated Sand for Copper (II) Removal from Water in Batch Mode

Abstract: Abstract:Removal of heavy metals, such as copper ions, from water is important to protect human health and the environment. In this study, manganese coated sand (MCS) was used as an adsorbent to remove copper ions in a batch system. Equilibrium data were determined at a temperature of 25.6 °C and the Langmuir model was used to describe the experimental data. Mn-coating improved the removal of copper ions by 70% as compared to uncoated sand. Based on a kinetics study, the adsorption of copper ions on MCS was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Although chemical precipitation is one of the methods that is most often used to remove copper ions, it has the disadvantage that it requires a large amount of chemicals in order to reduce metals to an allowable level for discharge [24]. Compared to the chemical precipitation technique, adsorption can remove metals over a wider pH range and at lower concentrations [25]. It has been demonstrated by several studies that the chemical precipitation method is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although chemical precipitation is one of the methods that is most often used to remove copper ions, it has the disadvantage that it requires a large amount of chemicals in order to reduce metals to an allowable level for discharge [24]. Compared to the chemical precipitation technique, adsorption can remove metals over a wider pH range and at lower concentrations [25]. It has been demonstrated by several studies that the chemical precipitation method is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, various forms of metal oxides (iron, manganese) have shown effective functionalization over the sand particles which delivered better removal of metals and organic pollutants as compared to sand (Lai and Chen, 2001;Rachmawati et al, 2013). Also, MC-LR carries a negative charge (pH: 2.1-10.2) in water and is expected to get attracted towards metal oxide surface because of the possible positive charge interface.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide-coated sands have been used for removing various heavy metals from water via the sorption mechanism [9]. For example, iron oxides are well-known to give a powerful effect on heavy metal sorption [10].…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide-and manganese oxide-coated sand (IOCS and MOCS) have been used as permeable reactive barrier (PRB) materials for treating heavy metal contamination in groundwater due to their ability to sorb various heavy metals, low-cost installation, and sustainable characteristics, replaceability, and long life-time [13]. Several studies reported that IOCS was satisfactory in removing Pb(II) [10], Cr(VI) and As(VI) [14], As(III) [15], Mo(VI) [16], and Cu(II) [17], whereas MOCS was effective in removing Cu(II) [9], Cr(VI), Pb(II), and Cd [12], and As(III) and As(VI) [18]. However, few studies have investigated the sorption of Ni and Zn onto IOCS and MOCS [11,17,19].…”
Section: Introductionmentioning
confidence: 99%